Effects of information technology capabilities on strategic alliances: Implications for the resource-based view - Lioukas,CS; Reuer,JJ; Zollo,M (Journal of Management Studies, 2016)
This paper adopts a contingency approach to the resourcebased view (RBV) of the firm and seeks to establish boundary conditions for the value of certain information technology (IT) capabilities. We first identify interorganizational alliances as a specific strategy context in which IT capabilities are particularly valuable. We then consider more detailed boundary conditions that can shape the value of these capabilities within the alliance context. Our study shows that firms with better IT capabilities can derive greater value from an alliance, yet this effect also varies across different types of alliances depending on an individual alliance's characteristics. Specifically, IT capabilities are more valuable for alliances with a nonequity governance structure, as well as those involving a high degree of interdependence between partners. We highlight the implications of our findings for opportunities to advance the RBV.